German dictionary German-English English-German revised and updated - Martin, Genevieve A; Bertram, Theodor; Kleinmann, Walter (New York Crown, 1993)
A language course in German and English developed for rapid learning and stressing conversationally useful words and phrases
Keywords: English language; German language